Identification of Potentially Pathogenic Bacteria in Fresh Marine Fish Sold at Kebon Roek Market, Mataram - Baiq Kesy Juliani; Sarkono; Bambang Fajar Suryadi (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to enumerate, detect, and identify potentially pathogenic bacteria contaminating fresh marine fish sold at Kebon Roek Market, Mataram City. This preliminary laboratory-based descriptive survey focused on the fish species most frequently purchased by consumers: eastern little tuna (Euthynnus sp.), sardinella (Sardinella sp.), and Indian mackerel (Rastrelliger sp.). Fish samples were collected from nine purposively selected vendors located in different sections of the market, comprising three vendors each from the front, middle, and rear areas. Laboratory analyses included determination of the Total Plate Count (TPC), bacterial isolation using selective media, and bacterial identification based on cellular morphology, Gram-staining reactions, and biochemical characteristics. The bacterial loads were 3.36 × 10⁶ CFU/g in eastern little tuna, 1.76 × 10⁶ CFU/g in Indian mackerel, and 4.85 × 10⁵ CFU/g in sardinella. The bacterial counts detected in eastern little tuna and Indian mackerel exceeded the maximum limits specified in the Indonesian National Standard SNI 7388:2009. Bacterial identification revealed the presence of potentially pathogenic bacteria, including Enterobacter spp., Citrobacter spp., Escherichia coli, Edwardsiella spp., Vibrio spp., and Aeromonas spp. These findings indicate that fresh marine fish sold at Kebon Roek Market may serve as a vehicle for transmitting pathogenic bacteria to consumers. Therefore, improved hygiene and sanitation practices are required throughout the fish distribution and retail chain to ensure food safety.